Rab11a Controls Cell Shape via C9orf72 Protein: Possible Relationships to Frontotemporal Dementia/Amyotrophic Lateral Sclerosis (FTDALS) Type 1 - Shoya Fukatsu; Hinami Sashi; Remina Shirai; Norio Takagi; Hiroaki Oizumi; Masahiro Yamamoto; Katsuya Ohbuchi; Yuki Miyamoto; Junji Yamauchi (Pathophysiology, 2024)
Abnormal nucleotide insertions of C9orf72, which forms a complex with Smith–Magenis syndrome chromosomal region candidate gene 8 (SMCR8) protein and WD repeat-containing protein 41 (WDR41) protein, are associated with an autosomal-dominant neurodegenerative frontotemporal dementia and/or amyotrophic lateral sclerosis type 1 (FTDALS1). The differentially expressed in normal and neoplastic cells (DENN) domain-containing C9orf72 and its complex with SMCR8 and WDR41 function as a guanine-nucleotide exchange factor for Rab GTP/GDP-binding proteins (Rab GEF, also called Rab activator). Among Rab proteins serving as major effectors, there exists Rab11a. However, it remains to be established which Rab protein is related to promoting or sustaining neuronal morphogenesis or homeostasis. In this study, we describe that the knockdown of Rab11a decreases the expression levels of neuronal differentiation marker proteins, as well as the elongation of neurite-like processes, using N1E-115 cells, a well-utilized neuronal differentiation model. Similar results were obtained in primary cortical neurons. In contrast, the knockdown of Rab11b, a Rab11a homolog, did not significantly affect their cell morphological changes. It is of note that treatment with hesperetin, a citrus flavonoid (also known as Vitamin P), recovered the neuronal morphological phenotypes induced by Rab11a knockdown. Also, the knockdown of Rab11a or Rab11b led to a decrease in glial marker expression levels and in morphological changes in FBD-102b cells, which serve as the oligodendroglial differentiation model. Rab11a is specifically involved in the regulation of neuronal morphological differentiation. The knockdown effect mimicking the loss of function of C9orf72 is reversed by treatment with hesperetin. These findings may reveal a clue for identifying one of the potential molecular and cellular phenotypes underlying FTDALS1.